A study of anti-SARS-CoV-2 antibody positivity in Duhok City, Iraq - Hussein, Nawfal R; Shahab, Guleer H; Rasheed, Narin A; Ahmed, Alind N; Salih, Reving S; Mahdi, Ahmed S; Mansour, Sabeeha A; Mahdi, Shaveen; Naqid, Ibrahim A; Ibrahim, Nawshan; Musa, Dildar H; Saleem, Zana SM (The Journal of Infection in Developing Countries, 2023)
Introduction: The study aimed to investigate the positivity rate of anti-SARS-CoV-2 antibodies and associated factors. Methodology: Data and blood samples were collected between January 10th and December 30th, 2021 based on COVID-19 infection by using a designated questionnaire. The blood samples were used for the detection of total SARS-CoV-2 antibodies. Results: 743 participants were recruited and 62.58% of them were positive for SARS-CoV-2 antibodies. Among these, 56.34% denied any symptoms of COVID-19. A higher positivity rate was found among females than men (OR = 1.5, CI = 1.1-2.0, p = 0.0073). Participants that had been diagnosed with COVID-19 in the past had a significantly higher prevalence of antibodies, and were nearly four times more likely to develop antibodies (OR = 4.0, CI = 2.4-6.8, p < 0.0001). Interestingly, only 3% of the participants with previous COVID-19 were seronegative while 46.54% were positive for antibodies without having a history of COVID-19 infection. Participants that reported symptoms were 2.6 times more likely to develop antibodies (OR = 2.6, CI = 1.9-3.6, p < 0.0001). Lastly, we found age to be significantly associated with the production of antibodies (CI = 13.3-14.7, p < 0.0001). Conclusions: The information from this study can be used to mitigate and develop tailored vaccination efforts and plan evidence-based strategies to better mitigate the ongoing COVID-19 pandemic in Kurdistan-Iraq.